2020
DOI: 10.3390/safety6020027
|View full text |Cite
|
Sign up to set email alerts
|

Roadside Fixed-Object Collisions, Barrier Performance, and Fatal Injuries in Single-Vehicle, Run-Off-Road Crashes

Abstract: Objectives: To quantify the odds of fatal injuries associated with drivers involved in single-vehicle, run-off-road (SVROR), injury crashes. Methods: An in-service safety evaluation was carried out using multivariate logistic regression models. Results: The odds of motorist death was lower for w-beam guardrail crashes as compared to tree, pole, and concrete barrier crashes. On the other hand, there was no statistically significant difference between the odds of motorist death in concrete barrier crashes as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The first model included all SVROR-injury crashes, the second model excluded free-collision events, and the last model excluded not only free-collision events but also curb crashes. The findings from a previous study, based on the same dataset used in the present research, found that collision-free events and curb crashes tend to be less severe than tree/pole/barrier crashes (Albuquerque & Awadalla, 2020a). Thus, excluding collision-free events and curb crashes is important in order to more accurately quantify the impact that HLO may have on crash severity.…”
Section: Impact Of Hazard Lateral Offset (Hlo) On Fatality Riskmentioning
confidence: 67%
See 3 more Smart Citations
“…The first model included all SVROR-injury crashes, the second model excluded free-collision events, and the last model excluded not only free-collision events but also curb crashes. The findings from a previous study, based on the same dataset used in the present research, found that collision-free events and curb crashes tend to be less severe than tree/pole/barrier crashes (Albuquerque & Awadalla, 2020a). Thus, excluding collision-free events and curb crashes is important in order to more accurately quantify the impact that HLO may have on crash severity.…”
Section: Impact Of Hazard Lateral Offset (Hlo) On Fatality Riskmentioning
confidence: 67%
“…Thus, excluding collision-free events and curb crashes is important in order to more accurately quantify the impact that HLO may have on crash severity. Furthermore, barrier crashes were also excluded from the data used in the models shown in Table 5, as previous research using the same dataset used in the present research showed that w-guardrail crashes are less severe than tree/ pole crashes (Albuquerque & Awadalla, 2020a). This is also relevant because CZ width policy aims at addressing locations with hazards such as trees and poles instead of barriers.…”
Section: Impact Of Hazard Lateral Offset (Hlo) On Fatality Riskmentioning
confidence: 92%
See 2 more Smart Citations
“…This study found that 65% of the crash sites investigated warranted a barrier but one was not installed, while 80% (see Table 5) of all crash sites investigated did not meet roadside design guidelines for barrier placement. This is relevant considering that past research has shown that the odds of fatal injuries occurring in pole and tree crashes are significantly higher than the odds of fatal injuries occurring in guardrail crashes [36].…”
Section: Practitioners and Road Safety Equipment Suppliersmentioning
confidence: 99%